2005
DOI: 10.1021/jp045213f
|View full text |Cite
|
Sign up to set email alerts
|

Ar-Matrix IR Spectra of 5-Halouracils Interpreted by Means of DFT Calculations

Abstract: The infrared low-temperature Ar-matrix spectra of 5-halouracils and unsubstituted uracil were measured and interpreted in terms of the spectra calculated at the DFT/B3PW91/6-311G level followed by a potential energy distribution (PED) analysis. For the PED analysis, the sets of halouracil mode definitions were constructed so that dissimilarities in the interpretations of the different spectra were minimized. Anharmonic frequency calculations enabled more light to be shed on the Fermi resonance (FR) phenomena o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 58 publications
2
30
0
3
Order By: Relevance
“…23 -25 From spectroscopy point of view, 5-BrU in the gas phase has been studied by several experimental techniques, such as dissociative electron attachment (DEA), 26 electronic absorption and fluorescence emission spectra, 27,28 NMR 29,30 and ESR. 41 However, the present work on 5-BrU remarkably improves upon the earlier results, identifying all the bands for the first time and reviewing the assignments of several bands. 38,39 In our previous work, IR and Raman studies on this molecule have also been reported, but again without theoretical support.…”
Section: Introductionsupporting
confidence: 67%
“…23 -25 From spectroscopy point of view, 5-BrU in the gas phase has been studied by several experimental techniques, such as dissociative electron attachment (DEA), 26 electronic absorption and fluorescence emission spectra, 27,28 NMR 29,30 and ESR. 41 However, the present work on 5-BrU remarkably improves upon the earlier results, identifying all the bands for the first time and reviewing the assignments of several bands. 38,39 In our previous work, IR and Raman studies on this molecule have also been reported, but again without theoretical support.…”
Section: Introductionsupporting
confidence: 67%
“…The peaks at 1771 and 1723 cm À1 are assigned to the carbonyl vibrational bands for the C2 and C4 carbonyl groups, respectively, through a comparison with the FTIR spectrum of 5-FU in an Ar-matrix [35]. The peak at 1665 cm À1 is assigned to the C5@C6 stretching mode of 5-FU and the peak at 1245 cm À1 is assigned to the C-F bending vibration according to the literature [29,[35][36][37]. The HY samples loaded with 5-FU have characteristic vibrations at 1756, 1717, 1690 and 1247 cm À1 .…”
Section: Ftir and Nmr Resultsmentioning
confidence: 99%
“…Uracil derivatives exhibit significant pharmacological activity, thereby attracting many workers for vibrational studies [1][2][3][4][5][6]. 6-Methyluracil (6MU) has been found to accelerate healing of burn wounds [7] and effects the regulation of lipid peroxidation [8].…”
Section: Introductionmentioning
confidence: 99%
“…(Ring), Q (C 6 -CH3 ), Q (C 4 -C5 ) experimental spectrum have been assigned to Q (N 1 -H 15 ) and Q (N 3 -H 14 ) respectively. These characteristic vibrational frequencies are shifted from the vapour spectrum and calculated frequencies, which may be due to the occurrence of intermolecular hydrogen bonding in solid state sample of 6MU.…”
mentioning
confidence: 99%